Confined synthesis of silicalite-1 hollow spheres with a lamellar shell. (15th January 2015) - Chen, Huiyong; Liu, Xiaotong; Ma, Xiaoxun
Abstract : A novel synthesis strategy involving the integrated use of soft/hard templates was proposed for the confined synthesis of silicalite-1 hollow spheres with a lamellar shell. Replicated from macroporous carbon templates and directed by multi-quaternary ammonium surfactants, these silicalite-1 spheres exhibit a unique hollow nanoshell morphology, high crystallinity, and a novel hierarchical porosity consisting of hollow macropores, interlamellar mesopores and ordered micropores in zeolites.